Analisis Kebebasan Bergama Yang Dianut Oleh Setiap Manusia Yang Terkait Dengan Hak Pada Manusia. - Faturohman Faturohman; Anisa Bela Fitri; Meli Andriyani (Lembaga Pengembangan Kinerja Dosen, 2024)
The revival of thinking about religious freedom as an integral part of human rights has become an increasingly important topic of discussion in the current global context. Human Rights are rights that are very inherent in every human being, especially every individual. In Indonesia, religious freedom which is linked to human rights has been regulated in statutory regulations. The content of the law is to emphasize that a country can guarantee the freedom of every resident to practice their own religion. Some regions may have certain rules or norms that limit religious freedom, even though they are legally constitutional. Indonesia guarantees religious freedom, this still occurs in cases of human rights violations related to religious freedom in several places in Indonesia.